Divergence with gene flow across a speciation continuum of Heliconius butterflies - Supple, Megan A. (BMC Evol Biol, 2015)
BACKGROUND: A key to understanding the origins of species is determining the evolutionary processes that drive the patterns of genomic divergence during speciation. New genomic technologies enable the study of high-resolution genomic patterns of divergence across natural speciation continua, where taxa pairs with different levels of reproductive isolation can be used as proxies for different stages of speciation. Empirical studies of these speciation continua can provide valuable insights into how genomes diverge during speciation. METHODS: We examine variation across a handful of genomic regions in parapatric and allopatric populations of Heliconius butterflies with varying levels of reproductive isolation. Genome sequences were mapped to 2.2-Mb of the H. erato genome, including 1-Mb across the red color pattern locus and multiple regions unlinked to color pattern variation. RESULTS: Phylogenetic analyses reveal a speciation continuum of pairs of hybridizing races and incipient species in the Heliconius erato clade. Comparisons of hybridizing pairs of divergently colored races and incipient species reveal that genomic divergence increases with ecological and reproductive isolation, not only across the locus responsible for adaptive variation in red wing coloration, but also at genomic regions unlinked to color pattern. DISCUSSION: We observe high levels of divergence between the incipient species H. erato and H. himera, suggesting that divergence may accumulate early in the speciation process. Comparisons of genomic divergence between the incipient species and allopatric races suggest that limited gene flow cannot account for the observed high levels of divergence between the incipient species. CONCLUSIONS: Our results provide a reconstruction of the speciation continuum across the H. erato clade and provide insights into the processes that drive genomic divergence during speciation, establishing the H. erato clade as a powerful framework for the study of speciation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12862-015-0486-y) contains supplementary material, which is available to authorized users.